U KRUGOVIMA (Filološke studije, 2019)
This short article analyses a poem by one of the best Croatian poets of the 90's war generation, Tomica Bajsić (a world traveller and a war veteran volunteer, wounded and decorated several times), and suggests possible interpretations of his war experience and the overall presence of travel adventure in his poetry.